The role of the exopolyphosphatase PPX in avoidance by Neisseria meningitidis of complement-mediated killing. - Zhang, Q; Li, Y; Tang, C (2010)
The complement system is critical for immunity against the important human pathogen Neisseria meningitidis. We describe the isolation of a meningococcal mutant lacking PPX, an exopolyphosphatase responsible for cleaving cellular polyphosphate, a polymer of tens to hundreds of orthophosphate residues found in virtually all living cells. Bacteria lacking PPX exhibit increased resistance to complement-mediated killing. By site directed mutagenesis, we define amino acids necessary for the biochemical activity of meningococcal PPX, including a conserved glutamate (Glu(117)) and residues in the Walker B box predicted to be involved in binding to phosphate. We show that the biochemical activity of PPX is necessary for interactions with the complement. The relative resistance of the ppx mutant does not result from changes in structures (such as capsule, lipopolysaccharide, and factor H-binding protein), which are known to be required for evasion of this key aspect of host immunity. Instead, expression of PPX modifies the interaction of N. meningitidis with the alternative pathway of complement activation.